Targeting Pathogenic Biofilms: Newly Developed Superhydrophobic Coating Favors a Host-Compatible Microbial Profile on the Titanium Surface - Souza, João G. S.; Bertolini, Martinna; Costa, Raphael C.; Cordeiro, Jairo M.; Nagay, Bruna E.; De Almeida, Amanda B.; Retamal-Valdes, Belén; Nociti, Francisco H.; Feres, Magda; Rangel, Elidiane C. [UNESP]; Barão, Valentim A. R. (American Chemical Society (ACS), 2020)
Polymicrobial infections are one of the most common reasons for inflammation of surrounding tissues and failure of implanted biomaterials. Because microorganism adhesion is the first step for biofilm formation, physical-chemical modifications of biomaterials have been proposed to reduce the initial microbial attachment. Thus, the use of superhydrophobic coatings has emerged because of their anti-biofilm properties. However, these coatings on the titanium (Ti) surface have been developed mainly by dual-step surface modification techniques and have not been tested using polymicrobial biofilms. Therefore, we developed a one-step superhydrophobic coating on the Ti surface by using a low-pressure plasma technology to create a biocompatible coating that reduces polymicrobial biofilm adhesion and formation. The superhydrophobic coating on Ti was created by the glow discharge plasma using Ar, O2, and hexamethyldisiloxane gases, and after full physical, chemical, and biological characterizations, we evaluated its properties regarding oral biofilm inhibition. The newly developed coating presented an increased surface roughness and, consequently, superhydrophobicity (contact angle over 150°) and enhanced corrosion resistance (p < 0.05) of the Ti surface. Furthermore, proteomic analysis showed a unique pattern of protein adsorption on the superhydrophobic coating without drastically changing the biologic processes mediated by proteins. Additionally, superhydrophobic treatment did not present a cytotoxic effect on fibroblasts or reduction of proliferation; however, it significantly reduced (≈8-fold change) polymicrobial adhesion (bacterial and fungal) and biofilm formation in vitro. Interestingly, superhydrophobic coating shifted the microbiological profile of biofilms formed in situ in the oral cavity, reducing by up to ≈7 fold pathogens associated with the peri-implant disease. Thus, this new superhydrophobic coating developed by a one-step glow discharge plasma technique is a promising biocompatible strategy to drastically reduce microbial adhesion and biofilm formation on Ti-based biomedical implants.
Keywords: biocompatibility; biofilm; biomaterials; hydrophobicity; titanium